Pseudocapacitive Storage in High-Performance Flexible Batteries and Supercapacitors - Zhenxiao Lu; Xiaochuan Ren (Batteries)
Attention to electrochemical energy storage (EES) devices continues to grow as the demand increases for energy storage systems in the storage and transmission of renewable energy. The expanded market requirement for mobile electronics devices and flexible electronic devices also calls for efficient energy suppliers. EES devices applying pseudocapacitive materials and generated pseudocapacitive storage are gaining increasing focus because they are capable of overcoming the capacity limitations of electrical double-layer capacitors (EDLCs) and offsetting the rate performance of batteries. The pseudocapacitive storage mechanism generally occurs on the surface or near the surface of the electrode materials, which could avoid the slow ion diffusion process. Developing materials with beneficial nanostructures and optimized phases supporting pseudocapacitive storage would efficiently improve the energy density and charging rate for EES devices, such as batteries and flexible supercapacitors. This review offers a detailed assessment of pseudocapacitance, including classification, working mechanisms, analysis methods, promotion routes and advanced applications. The future challenges facing the effective utilization of pseudocapacitive mechanisms in upcoming energy storage devices are also discussed.